(untitled) (International Seven Journal of Multidisciplinary, 2023)
This study discussed opinions on high abilities in students. The aim was to understand the universe of individuals with high abilities/ giftedness (HS/G) using the qualitative method with bibliographical and exploratory research into various databases such as Scielo and Google Scholar. The subject has complex reflections due to the heterogeneity of this group. Children and young people with high abilities and giftedness may have different educational and emotional needs, resulting from their cognitive complexity, greater intensity of response, emotional sensitivity, among other factors. They may display worrying behaviors such as social maladjustment and insecurity which, if left unaddressed, can lead to socio-emotional risks. It is important to understand the cognitive, emotional, affective and social world of gifted individuals in order to reduce their vulnerabilities and understand their way of acting in the world.